Significance of Indicators of Dermatoglyphics of Fingers and Palm - Asrorov Akmal Aminjonovich (Scientific Trends, 2024)
In this article, the understanding of what dermatoglyphics studies, what are its sections, what can be studied in these sections, and the importance of finger and palm dermatoglyphics indicators is fully explained.
Keywords: Dermatoglyphics, palmoscopy, dactyloscopy, distal, proximal, tenor, hypotenor, ulnar, arcuate, loop, circular.